A new abietane-type diterpenoid and a new long-chain alkenone from fungus Daldinia sp. TJ403-LS1. Issue 2 (17th January 2022) - Lin, Shuang; Zhang, Xueke; Shen, Ling; Mo, Shuyuan; Liu, Junjun; Wang, Jianping; Hu, Zhengxi; Zhang, Yonghui
Abstract: A new abietane-type diterpenoid, dalterpenoid A (1 ), a new long-chain alkenone derivative, (3 E, 5 E, 10 E )-8-hydroxytrideca-3, 5, 10, 12-tetraen-2-one (2 ), together with six known compounds (3 –8 ), namely epi -guaidiol A (3 ), xylaranol A (4 ), daldinone C (5 ), trans -3, 4-dihydroxy-3, 4-dihydro-anofinic acid (6 ), ( R )-6-hydroxymellein (7 ), helicascolide A (8 ), were obtained from fungus Daldinia sp. TJ403-LS1, which was originally isolated from roots of the medicinally valuable plant Anoectochilus roxburghii . The structures of compounds 1 and 2 were established based on widespread spectroscopic methods, mainly including 1D & 2D NMR and HRESIMS analyses, and the absolute configuration of 1 was further confirmed by electronic circular dichroism (ECD) calculation. All new compounds were tested for the in vitro cytotoxicity against five human cancer cell lines. Abstract : UF0001